ANALYSIS OF COAL EXPORT DEVELOPMENT IN ACEH PROVINCE THROUGH RCA AND MCI APPROACH - Khalish Khairina; Angga Syahputra (LPPM Press STIE Indragiri Rengat, 2021)
This study aims to analyze the development of coal’s export in Aceh Province by using Revealed Comparative Advantage (RCA) and Market Concentration Index (MCI). This study is descriptive quantitave research by using time series data for 6 years (2015 -2020), used data is value export of Aceh. RCA is used to analyze the competitive of coal, whereas, MCI is used to analyze the ployment of coal’s export. RCA Index, since 2015 – 2019, is under 1 that means coal in Aceh has low competitiveness. RCA index in 2020, shows at 1,06 which means coal in Aceh has high competitiveness. MCI Index for Aceh’s coal always shows close to 1, which mean that coal’s export only concentrated to one country and coal’s export in Aceh is unscattered.